Perceived Prejudice and the Mental Health of Chinese Ethnic Minority College Students: The Chain Mediating Effect of Ethnic Identity and Hope - Yao, Jin; Yang, Liping (Frontiers in Psychology, 2017)
As a multinational country incorporating 56 officially recognized ethnic groups, China is concerned with the mental health of members of minority ethnic groups, with an increasing focus on supporting Chinese ethnic minority college students. Nevertheless, in daily life, members of minority ethnic groups in China often perceive prejudice, which may in turn negatively influence their mental health, with respect to relative levels of ethnic identity and hope. To examine the mediating effects of ethnic identity and hope on the relationship between perceived prejudice and the mental health of Chinese ethnic minority college students, 665 students (18–26 years old; 207 males, 458 females; the proportion of participants is 95.38%) from nine colleges in the Guangxi Zhuang autonomous region and Yunnan and Guizhou provinces of China took part in our study, each completing adapted versions of a perceived prejudice scale, a multiethnic identity measure, an adult dispositional hope scale, and a general health questionnaire. Analysis of the results reveals that perceived prejudice negatively influences mental health through both ethnic identity and hope in Chinese ethnic minority college students. The total mediation effect was 54.9%. Perceived prejudice was found to negatively predict ethnic identity and hope, suggesting that perceived prejudice brings about a negative reconstruction of ethnic identity and hope mechanisms within the study’s Chinese cultural context. The relationship between perceived prejudice and mental health was fully mediated by hope and the chain of ethnic identity and hope. Ethnic identity partially mediated the relationship between perceived prejudice and hope. The relationship between perceived prejudice and mental health mediated by ethnic identity was not significant, which suggests that the rejection–identification model cannot be applied to Chinese ethnic minority college students. This paper concludes by considering the limitations of our study and discussing the implications of its results for researchers and practitioners.